Giorgione stupisce Tiziano e Giovanni Bellini di Cesare dell’Acqua - Panizon, Ermanna (MDCCC 1800, 2022)
This article aims at presenting a painting by Cesare dell’Acqua (Piran 1821-Bruxelles 1905) as an interesting example of the nineteenth-century genre of history painting depicting scenes from the lives of Renaissance artists. The analysis of this work, that has never been examined by the critics, will concentrate on Giorgione’s fortuna in ninteenth-century Venice, especially as a subject of this genre of representation. The painting was exhibited at the Cercle Artistique et Litteraire di Bruxelles in 1861 with the title Giorgione stupisce Tiziano e Giovanni Bellini and is today held in a private collection in Trieste. Cesare dell’Acqua has depicted Giorgione in the act of painting under the gaze of a boy, Titian, and an old man, Giovanni Bellini. Dell’Acqua’s work thus presents the triad of Venetian Renaissance art highlighting Giorgione's pivotal role and reflecting an iconographic theme that is typical of Venetian and Giorgione's painting, the 'Three Ages of Man'. The contribution analyses the visual and literary sources of dell’Acqua’s composition and compares it with other coeval paintings of the same genre, with the aim of deepening the fortuna of Renaissance artists through this new evidence.